2014
DOI: 10.3892/or.2014.3289
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin C enhances anticancer activity in methotrexate-treated Hep3B hepatocellular carcinoma cells

Abstract: Methotrexate (MTX) has been widely used for rheumatoid arthritis therapy for a long time. MTX is also used as an anticancer drug for various tumors. However, many studies have shown that high-dose MTX treatment for cancer therapy may cause liver and renal damage. Alhough the mechanisms involved in MTX-induced liver and renal damage require further research, many studies have indicated that MTX-induced cytotoxicity is associated with increases in oxidative stress and caspase activation. In order to reduce MTX-i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
32
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 62 publications
6
32
0
Order By: Relevance
“…In addition, MTX has been applied for clinical cancer treatment (13,14). Previous studies demonstrated that MTX can inhibit the growth of various cancer cells, including hepatoma, leukemia, lymphoma and gastric cancer cells (15)(16)(17). Nevertheless, MTX alone is not effective for breast cancer treatment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, MTX has been applied for clinical cancer treatment (13,14). Previous studies demonstrated that MTX can inhibit the growth of various cancer cells, including hepatoma, leukemia, lymphoma and gastric cancer cells (15)(16)(17). Nevertheless, MTX alone is not effective for breast cancer treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Vitamin C, a common nutrient, has anti-oxidative (26,27) and anticancer activities (28,29). Previous studies have also demonstrated that combined treatment with vitamin C and conventional anticancer agents can enhance anticancer activities (15,30,31). Currently, vitamin C supplements are being applied for clinical cancer therapy (32)(33)(34).…”
Section: Introductionmentioning
confidence: 99%
“…When AA is combined with a glycolysis inhibitor, 3-(3-pyridinyl)-1-(4-pyridinyl)-2-propen -1-one (3-PO), a synergistic induction of apoptosis via a ROSdependent pathway in non-small cell carcinoma cell lines (H1299, H661 and A549) was observed [13]. In addition, AA was shown to potentiate low dose methotrexate in inducing cancer cell death by caspase 3 and caspase 9 activation in hepatocellular carcinoma cells (Hep3B) [14].…”
Section: Ascorbic Acid Can Alter Intracellular Pathways and Cause Canmentioning
confidence: 97%
“…There are also reports indicating that AA can enhance the effectiveness of chemotherapeutic agents that can reduce the cytotoxicity of anticancer drugs, and also may prevent free radicals and neutralize some carcinogens [14,46,47]. The identification of the variety of responses to cancer therapy requires knowledge of variables, including concomitant medications, which may alter the metabolism and pharmacokinetics of chemotherapy.…”
Section: Discussionmentioning
confidence: 99%